Dinamika Politik Lokal: Nepotisme dan Konflik Internal di Pemerintah Desa Cinta Rakyat - Rahma Yani Hasibuan; Julia Ivanna (Journal on Education, 2024)
This research aims to examine local political dynamics related to the practice of nepotism and internal conflict in the Cinta Rakyat Village Government. The problems studied include an analysis of the factors that influence the emergence of nepotism and internal conflict in the context of village government, as well as their impact on the sustainability of local development and community trust in local government institutions. The research method used is a qualitative descriptive method using interviews, observation and documentation. Data analysis was carried out using a descriptive and interpretive approach to understand local political dynamics related to nepotism and internal conflict. The research results show that the practice of nepotism and internal conflict in the Cinta Rakyat Village Government is influenced by factors such as local power dynamics, socio-economic structure and political culture of the local community. Nepotism and internal conflict have hampered the effectiveness and sustainability of village development and reduced public trust in village government institutions. This research provides a deeper understanding of the complexity of local politics at the village level and highlights the importance of policy reform to overcome nepotism and internal conflict in local government in order to realize sustainable development and transparent and accountable government.